2012
DOI: 10.1227/neu.0b013e3182367124
|View full text |Cite
|
Sign up to set email alerts
|

Injuries of the Cingulum and Fornix After Rupture of an Anterior Communicating Artery Aneurysm

Abstract: We found injuries of the cingulum and fornix in patients with an ACoA aneurysm rupture. It is our belief that sustained memory impairment of patients with an ACoA aneurysm rupture might be related to injury of the cingulum and fornix. Therefore, we recommend evaluation of the cingulum and fornix with diffusion tensor tractography for patients with an ACoA aneurysm rupture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 30 publications
2
36
0
Order By: Relevance
“…The anterior cingulum has been associated with both verbal and visual spatial memory (Kantarci et al, 2011; Mielke et al, 2009) as well as the fornix (Mielke et al, 2009; Palacios et al, 2011). The cingulum and fornix are major components of the Papez circuit (Abdul-Rahman et al, 2011; Hong et al, 2012; Shah et al, 2012), a circuit known for the formation of new memories (episodic). Damage to this circuit results in anterograde amnesia (Thomas et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The anterior cingulum has been associated with both verbal and visual spatial memory (Kantarci et al, 2011; Mielke et al, 2009) as well as the fornix (Mielke et al, 2009; Palacios et al, 2011). The cingulum and fornix are major components of the Papez circuit (Abdul-Rahman et al, 2011; Hong et al, 2012; Shah et al, 2012), a circuit known for the formation of new memories (episodic). Damage to this circuit results in anterograde amnesia (Thomas et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Since introduction of DTI, many studies have investigated injury of the cingulum in various brain pathologies, including subarachnoid hemorrhage, traumatic brain injury, and hypoxic ischemic brain injury (Sugiyama et al, 2009; Wilde et al, 2010, 2011; Wu et al, 2010; McCauley et al, 2011; Wang et al, 2011; Hong et al, 2012; Lee et al, 2012; Baek et al, 2013; Sanjuan et al, 2013; Zheng et al, 2013). Most of these studies investigated injury of the cingulum using DTI parameters [Sugiyama et al, 2009; Wilde et al, 2010, 2011; Wu et al, 2010; McCauley et al, 2011; Wang et al, 2011; Hong et al, 2012; Lee et al, 2012; Sanjuan et al, 2013; Zheng et al, 2013 (Epub ahead of print)].…”
Section: Discussionmentioning
confidence: 99%
“…Most of these studies investigated injury of the cingulum using DTI parameters [Sugiyama et al, 2009; Wilde et al, 2010, 2011; Wu et al, 2010; McCauley et al, 2011; Wang et al, 2011; Hong et al, 2012; Lee et al, 2012; Sanjuan et al, 2013; Zheng et al, 2013 (Epub ahead of print)]. Only a few studies have reported that discontinuation of the anterior cingulum was related to cognitive dysfunction following brain injury (Baek et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…35 However, the authors did not analyze the sites of lesions or present the neuropsychological data of their cases. On the contrary, all our patients demonstrated infarction in the column of the fornix and underwent formal neuropsychological tests, which indicated their disproportionate impairment of memory but only limited intellectual decline [IQ Ϫ MQ ϭ 26 (mean), all Ͼ 15].…”
Section: Figmentioning
confidence: 99%